Euterpe oleracea Mart. (açaí) seeds show in vitro prebiotic potential: Integrative evidence from human colonic fermentation - Joanderson Gama Santos; Lucélia Cabral; Layane Rosa da Silva; Taliana Kênia Alencar Bezerra; Luiz Eduardo Lobo e Silva; Amanda Pereira da Silva; Lucimara Mach Côrtes Cordeiro; Marcos dos Santos Lima; Roger Wagner; Tatiana Colombo Pimentel; Marciane Magnani (Food Research International, 2026)

Glial remodeling and neuroprotective effects of L-glutamine supplementation on the enteric nervous system in walker-256 tumor-bearing rats - Sara Raquel Garcia de Souza; Juliana Vanessa Colombo Martins Perles; Gleison Daion Piovezana Bossolani; Érika Xavier Santos; Geraldo Emilio Vicentini; Luciane Fracaro; Fernanda Paschoal Blegniski; Flávia Alessandra Guarnier; Emerson Barili; Flávia Cristina Vieira Frez; Camila Caviquioli Sehaber; Mariana Machado Lima; et al. (Tissue and Cell, 2026)

Isotopic insights into the fate of atmospheric nitrogen in alpine tundra ponds with contrasting land cover and cryospheric conditions - R. Balestrini; N. Colombo; M. Freppaz; M.F. Lehmann; C. Delconte; E. Pintaldi; F. Salerno; I. Matiatos (CATENA, 2026)

Toward Sustainable Rainbow Trout Lipid Nutrition: A Systematic Review of Lipid Optimization Strategies in Controlled Conditions - Rosendo L. Azcuy; Alejandro Villasante; Susana Perelman; Matías E. Casaretto; Patricio Dantagnan; Gabriel A. Morales; Stefanie Colombo (Reviews in Aquaculture, 2026)
Replacing fish oil (FO) in feeds remains a challenge for aquaculture sustainability. While experimental studies have evaluated the effects of alternative lipids on fillet long‐chain polyunsaturated fatty acids (LC‐PUFA) in rainbow trout, a quantitative synthesis of these effects is lacking. Here, 119 experimental diets from 29 controlled studies were synthesized through a statistical framework combining linear mixed‐effects models (LMM), generalized additive models (GAM), and leave‐one‐study‐out validation. Dietary docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) consistently predicted fillet DHA and EPA concentrations, independent of growth rate and not significantly influenced by temperature or lipid level. While growth performance was unaffected by FO replacement, LC‐PUFA deposition was not equivalent across lipid origins: FO and vegetable‐based diets supported steeper diet‐to‐fillet transfer slopes compared to animal‐derived lipids. GAMs revealed non‐linear thresholds, with active deposition occurring only when dietary LC‐PUFA exceeded near 10 mg g −1 and the dietary n‐6:n‐3 ratio remained below approximately 4. Temperature, modelled linearly, showed no significant effect on fillet LC‐PUFA deposition within the analysed dataset. These results demonstrate that FO can be reduced without compromising growth, but not without reformulating LC‐PUFA supply and precursor balance. Successful FO replacement is therefore a formulation problem rather than an ingredient substitution issue. Emerging sources such as algal oils or engineered oilseeds represent a viable pathway toward sustainable feeds delivering nutritionally valuable fillets. The identified dietary thresholds provide practical guidance for feed formulation by defining minimum LC‐PUFA inclusion levels and n‐6:n‐3 ratios required to achieve target fillet EPA and DHA concentrations under controlled temperature conditions.

Predicting acute developmental toxicity of chemicals in embryos of the African clawed frog (Xenopus laevis): Calibration and validation of regression-based quantitative structure activity relationship models for hazard assessment of chemicals in anuran amphibians - Christian Novello; Matteo Riccardo Di Nicola; Jean Lou CM Dorne; Erika Colombo; Edoardo Luca Viganò; Manuel E. Ortiz-Santaliestra; Nynke Kramer; Edoardo Carnesecchi; Anna Melina Steinbach; Ivano Eberini; Antony Williams; Emilio Benfenati; et al. (Toxicology Letters, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Single-cell protein meal produced from Methylovorus menthalis (Psomi™) in extruded aquafeeds for seawater phase Atlantic salmon (Salmo salar L.): Impacts on growth performance, nutrient utilization, fish health, and fillet quality - Sean M. Tibbetts; André Dumas; Van Pham Thi Ha To; Ivan Tankovski; Noppawan Chimsung; Shane J.J. Patelakis; Stefanie M. Colombo; Talia Boates; Roberto E. Armenta; Brianna Orr Stratton (Aquaculture, 2026)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

Aspartic proteases from Silybum marianum: different plant-specific inserts, different destinations - M. Laura Colombo; Agustina Fernández; Constanza S. Liggieri; Pablo Tornero; Laura S. Bakás; Sandra E. Vairo-Cavalli (Planta, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Mechanistic aspects of the binding of acid–base ligands to ferric heme proteins - Andresa Messias; Melisa Carllinni Colombo; Juan Cruz Palermo; Jonathan A. Córdova; Giovanna De Simone; Paolo Ascenzi; Darío A. Estrin; Luciana Capece; Sara E. Bari (Biophysical Reviews, 2025)

Low prevalence of microplastic contamination in the bottom sediments and deep-sea waters of the Bransfield strait, Antarctica - Gabriel Enrique De-la-Torre; Ana D. Forero López; Carolina V. Colombo; Guido N. Rimondino; Fabio E. Malanca; Martha Barahona; Luis Santillán (Chemosphere, 2024)

LP-38 DockTox: a molecular docking platform for screening small molecules targeting Molecular Initiating Events (MIEs) relevant to liver, kidney and brain adverse events - R. Ortega Vallbona; D. Talavera Cortés; L.E. Carpio Mulas; E. Colombo; A. Roncaglioni; M. Garcia de Lomana; E. Benfenati; D. Gadaleta; R. Gozalbes; E. Serrano Candelas (Toxicology Letters, 2024)

Retrieval of snow liquid water content from radiative transfer model, field data and PRISMA satellite data - C. Ravasio; R. Garzonio; B. Di Mauro; E. Matta; C. Giardino; M. Pepe; E. Cremonese; P. Pogliotti; C. Marin; R. Colombo (Remote Sensing of Environment, 2024)

High-Resolution In Situ Characterization of the Hydrochemical Variability Along the Fluvio-marine Transition of the Río de la Plata Estuary, Argentina - S. Heguilor; E. D. Speranza; L. M. Tatone; C. N. Skorupka; M. C. Migoya; J. C. Colombo (Estuaries and Coasts, 2024)

High-resolution temporal variations of nitrate in a high-elevation pond in alpine tundra (NW Italian Alps) - N. Colombo; R. Balestrini; D. Godone; D. Vione; D. Said-Pullicino; G. Viviano; M. Martin; C.A. Delconte; S. Fratianni; A.G. Capodaglio; E. Pintaldi; M. Freppaz; et al. (CATENA, 2024)

P25-21: Approach and challenges in the toxicological and allergenicity risk assessment of novel proteins and their sources - I. Nuin Garciarena; O. Albert; P. Colombo; A. Fernández Dumont; M. Laganaro; A. Muñoz González; E. Noriega Fernández; G. Precup; R. Roldán Torres; A. Rossi; E. Ververis; A. Germini; et al. (Toxicology Letters, 2023)

OS04-02: Next Generation PBK modeling with PK-Sim for the prediction of chemical distribution in humans - R. Geci; D. Gadaleta; S. Proença; E. Colombo; M. García de Lomana; R. Ortega Vallbona; N. Kramer; A. Paini; L. Küpfer; S. Schaller (Toxicology Letters, 2023)

Psilocybin prevents reinstatement of alcohol seeking by disrupting the reconsolidation of alcohol-related memories - F. Benvenuti; D. Colombo; L. Soverchia; N. Cannella; E. Domi; R. Ciccocioppo (Psychopharmacology, 2023)

Hydrological, thermal and chemical influence of an intact rock glacier discharge on mountain stream water - F. Bearzot; N. Colombo; E. Cremonese; U. Morra di Cella; E. Drigo; M. Caschetto; S. Basiricò; G.B. Crosta; P. Frattini; M. Freppaz; P. Pogliotti; F. Salerno; et al. (Science of The Total Environment, 2023)

: A high-order discontinuous Galerkin solver for flow simulations and multi-physics applications - E. Ferrer; G. Rubio; G. Ntoukas; W. Laskowski; O.A. Mariño; S. Colombo; A. Mateo-Gabín; H. Marbona; F. Manrique de Lara; D. Huergo; J. Manzanero; A.M. Rueda-Ramírez; et al. (Computer Physics Communications, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

The Gondwanide deformation along the southwestern border of the Río de la Plata Craton: Geochemical and geochronological constraints on ductile shear zones from the Ventania System basement, Argentina - Carlos A. Ballivián Justiniano; Sebastián Oriolo; Miguel A.S. Basei; Mabel E. Lanfranchini; Rodolfo O. Christiansen; Norberto J. Uriz; Sebastián E. Vázquez Lucero; Daniela A. Del Bono; Marnie A. Forster; Ricardo O. Etcheverry; Colombo C.G. Tassinari; Marcos A. Comerio; et al. (Journal of South American Earth Sciences, 2023)

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Sandstone petrofacies, deformational events and the dynamic of the Valle Fértil Lineament during the late Paleozoic (Paganzo Basin, northwestern Argentina) - Luis A. Spalletti; Carlos O. Limarino; Ferrán Colombo; Patricia L. Ciccioli; Carina E. Colombi (Journal of South American Earth Sciences, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evaluation of Infiltration Models with Different Numbers of Adjustment Parameters in an Oxisol with Application of Wastewater at the Different Concentrations - Júlia Fonseca Colombo Andrade; Luiz Fernando Coutinho de Oliveira; Jaíza Ribeiro Mota e Silva (Water, Air, & Soil Pollution, 2021)

The use of biomimetic tools for water quality monitoring: passive samplers versus sentinel organisms - M. Morrone; N. E. Cappelletti; L. M. Tatone; M. J. Astoviza; J. C. Colombo (Environmental Monitoring and Assessment, 2021)

Exposure to 17β estradiol causes erosion of sexual dimorphism in Bluegill (Lepomis macrochirus) - Neeta Parajulee Karki; Robert E. Colombo; Karen F. Gaines; Anabela Maia (Environmental Science and Pollution Research, 2021)

Gulliver’s virtual travels: active embodiment in extreme body sizes for modulating our body representations - S. Serino; F. Scarpina; A. Chirico; A. Dakanalis; D. Di Lernia; D. Colombo; V. Catallo; E. Pedroli; G. Riva (Cognitive Processing, 2020)
It is noted that the perceptual experience of body and space can be modulated by changing the action capabilities or by manipulating the perceived body dimensions through a multisensory stimulation. This study adds to pre-existing literature by investigating the alterations in bodily experience following embodiment to both enlarged and shrunked bodies, while participants actively navigated in a virtual environment. A normal-sized body served as a reference condition. After each embodied navigation, participants estimated the height and width of three different body parts. Results revealed that the embodiment over shrunked body induced a significant reduction in participants’ body image, while no changes were reported after the embodiment over the enlarged body. Findings were discussed in terms of previous literature exploring the constraints implicated in the ownership over different bodies.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Persistently warmer temperatures lead to life history changes in bluegill sunfish (Lepomis macrochirus) - Dalon P. White; Robert E. Colombo; David H. Wahl (Environmental Biology of Fishes, 2020)

Elucidating the symbiotic interactions between a locally isolated microalga Chlorella vulgaris and its co-occurring bacterium Rhizobium sp. in synthetic municipal wastewater - L. Ferro; M. Colombo; E. Posadas; C. Funk; R. Muñoz (Journal of Applied Phycology, 2019)

Synthesis and evaluation of the antileishmanial activity of silver compounds containing imidazolidine-2-thione - Patrícia Ferreira Espuri; Larissa Luiza dos Reis; Eduardo de Figueiredo Peloso; Vanessa Silva Gontijo; Fábio Antônio Colombo; Juliana Barbosa Nunes; Carine Ervolino de Oliveira; Eduardo T. De Almeida; Débora E. S. Silva; Jessica Bortoletto; Daniel Fonseca Segura; Adelino V. G. Netto; et al. (JBIC Journal of Biological Inorganic Chemistry, 2019)

In Situ Tissue Labeling of Cerebral Amyloid Using HIV-Related Tat Peptide - E. Maderna; L. Colombo; A. Cagnotto; G. Di Fede; A. Indaco; F. Tagliavini; M. Salmona; G. Giaccone (Molecular Neurobiology, 2018)

Promising primers for detection of phytoplasma causing coconut lethal yellowing disease in Mozambique - M. O. M. Mazivele; Valter Nuaila; M. Durante; M. M. Colombo; E. Taviani (Phytoparasitica, 2018)

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

Healthy and tumoral tissue resistivity in wild-type and sparc–/– animal models - D. Meroni; G. Mauri; D. Bovio; A. M. Bianchi; C. Chiodoni; M. P. Colombo; E. Meroni; A. Aliverti (Medical & Biological Engineering & Computing, 2016)

Effects of heated effluent on Midwestern US lakes: implications for future climate change - Joshua J. Mulhollem; Robert E. Colombo; David H. Wahl (Aquatic Sciences, 2016)

Fatty acid alterations in the detritivorous Prochilodus lineatus promoted by opportunistic feeding on sewage discharges in the R ío de la P lata estuary - E. D. Speranza; M. Colombo; L. M. Tatone; N. Cappelletti; M. C. Migoya; J. C. Colombo (Journal of Fish Biology, 2016)
Muscle fatty acid profiles and PCB contents of the detritivorous species Prochilodus lineatus and its diet (stomach contents, settling particles and sediments) were analysed from reference and polluted areas of the Paraná‐Rio de la Plata basin, to evaluate the alterations produced by opportunistic feeding on sewage discharges. Overall muscle fatty acid composition was dominated by saturated and monounsaturated 16 and 18 carbon (18 C‐ FA ) components with reduced long‐chain polyunsaturated fatty acids ( LC‐PUFA ). Compared to sediments, settling particles and stomach contents were enriched in lipids and had a similar fatty acid composition. Opportunistic feeding on sewage detritus at Buenos Aires resulted in enhanced PCB and triglyceride accumulation, with higher proportions of 18 C‐ FA and lower proportions of 16:1 and LC‐PUFA compared to fish from northern pristine reaches of the basin. Mid‐Paraná showed intermediate values reflecting mixing of the North stock with migrating Buenos Aires P. lineatus identified by their lipid and contaminant profile. According to multivariate analyses, this geographical variation of fatty acid composition was strongly influenced by PCB concentration. Prochilodus lineatus assimilates the energy subsidy of sewage inputs through enhanced lipogenesis with dominant 18 C‐ FA and significant amounts of valuable LC‐PUFA . This lipid alteration facilitates the bioaccumulation of PCBs which in turn may reinforce the adipogenic effect of sewage feeding.

A follow-up study examining airborne Ambrosia pollen in the Milan area in 2014 in relation to the accidental introduction of the ragweed leaf beetle Ophraella communa - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; Ł. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2016)

Properties and Mechanobiological Behavior of Bovine Nasal Septum Cartilage - Maria Rita Correro-Shahgaldian; Jasmin Introvigne; Chafik Ghayor; Franz E. Weber; Luigi M. Gallo; Vera Colombo (Annals of Biomedical Engineering, 2016)

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Is the recent decrease in airborne Ambrosia pollen in the Milan area due to the accidental introduction of the ragweed leaf beetle Ophraella communa? - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; L. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2015)

Bioaccumulation of dioxin-like PCBs and PBDEs by detritus-feeding fish in the Rio de la Plata estuary, Argentina - N. Cappelletti; E. Speranza; L. Tatone; M. Astoviza; M. C. Migoya; J. C. Colombo (Environmental Science and Pollution Research, 2015)

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

AtAPOSTART1, an Arabidopsis thaliana PH-START domain protein involved in seed germination - F. Resentini; S. Vanzulli; G. Marconi; L. Colombo; E. Albertini; S. Masiero (Plant Biosystems, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Protein interactions guiding carpel and fruit development in Arabidopsis - H. Herrera-Ubaldo; E. Zanchetti; L. Colombo; S. de Folter (Plant Biosystems, 2014)

Effects of Nicotine on Cardiovascular Remodeling in a Mouse Model of Systemic Hypertension - E. Sage Colombo; Joshua Davis; Mehran Makvandi; Mario Aragon; Selita N. Lucas; Michael L. Paffett; Matthew J. Campen (Cardiovascular Toxicology, 2013)

Seasonal course of photosynthetic efficiency in Larix decidua Mill. in response to temperature and change in pigment composition during senescence - M. Galvagno; M. Rossini; M. Migliavacca; E. Cremonese; R. Colombo; U. Morra di Cella (International Journal of Biometeorology, 2013)

Migratory behaviour of a dominant detritivorous fish Prochilodus lineatus evaluated by multivariate biochemical and pollutant data - E. D. Speranza; N. Cappelletti; M. C. Migoya; L. M. Tatone; J. C. Colombo (Journal of Fish Biology, 2012)
This paper studies the migration pathways and ranges of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Río de la Plata basin using multivariate analysis of biochemical and pollutant data. Biochemical composition (water, ash, lipids, proteins, carbohydrates, neutral lipids classes and fatty acids), aliphatic hydrocarbons (ALI), polychlorinated biphenyls (PCB), linear alkylbenzenes (LAB) and organochlorine pesticides (OClP) were determined in muscle samples of P. lineatus collected in Metropolitan Buenos Aires, the lower Paraná River (Paraná: 200–1000 km from Buenos Aires) and the middle Paraná and Paraguay Rivers (North: 1000–1400 km north). Biochemical variables and pollutants exhibited large variability [Lipids 1·1–89·5% wet mass; ALI 1·4–413; LABs not detectable (n.d.)–115·2; PCBs n.d.–27·9; OClPs n.d.–11·8 µg g −1 dry mass], due to the contrast of Buenos Aires with North fish. Fish from Buenos Aires were fatty (lipids 24·7 ± 12·3% wet mass), enriched in 18 carbon fatty acids and severely contaminated (ALI 152·4 ± 72·3; LABs 65·1 ± 26·4; PCBs 15·2 ± 6·8; OClPs 1·8 ± 1·9 µg g −1 dry mass mean ± s.d .). In contrast, fish from North were lean (4·1 ± 3·1% wet mass), enriched in long chain (>20 carbons) polyunsaturated fatty acids, with average one to two orders of magnitude lower pollutant levels (ALI 41·2 ± 51·9; PCBs 2·2 ± 3·5; LABs 8·8 ± 21·1; OClPs 0·67 ± 0·75 µg g −1 dry mass mean ± s.d .). Paraná showed intermediate values in all variables, denoting the mixing of different fish stocks. Based on principal component analysis, 14 outliers from 60 North and Paraná samples (representing 26 from 108 individual fish) were identified as pertaining to the Buenos Aires group with very similar lipid and pollutant levels. Data suggest that P. lineatus migrates a highly variable distance, exceeding 800–1000 km in multiple spatial and temporal overlapping ranges. Chemometric analysis of biochemical and pollutant data effectively discriminates fish according to the chemical signature acquired by detritus feeding in pristine and contaminated urban or industrial areas.

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Metamorphic P-T evolution of granulites in the central Ribeira Fold Belt, SE Brazil - Telmo M. Bento dos Santos; José M. Munhá; Colombo C. G. Tassinari; Paulo E. Fonseca; Coriolano Dias Neto (Geosciences Journal, 2011)

With time on our side? Task-dependent compensatory processes in graceful aging - M. Berlingeri; G. Bottini; L. Danelli; F. Ferri; D. Traficante; L. Sacheli; N. Colombo; M. Sberna; R. Sterzi; G. Scialfa; E. Paulesu (Experimental Brain Research, 2010)

Remote sensing of larch phenological cycle and analysis of relationships with climate in the Alpine region - L. BUSETTO; R. COLOMBO; M. MIGLIAVACCA; E. CREMONESE; M. MERONI; M. GALVAGNO; M. ROSSINI; C. SINISCALCO; U. MORRA DI CELLA; E. PARI (Global Change Biology, 2010)
This research aims at developing a remote sensing technique for monitoring the interannual variability of the European larch phenological cycle in the Alpine region of Aosta Valley (Northern Italy) and to evaluate its relationships with climatic factors. Phenological field observations were conducted in eight test sites from 2005 to 2007 to determine the dates of completion of different phenological phases. MODerate Resolution Imaging Spectrometer (MODIS) 250 m 16‐days normalized difference vegetation index (NDVI) time series were fitted with double logistic curves and the dates corresponding to different features of the curves were determined. Comparison with field data showed that the features of the fitted NDVI curve that allowed the best estimate of the start and end of the growing season were the zeroes of its third derivative (MAE of 6 and 4 days, respectively). The start and end of season were also estimated with the spring warming (SW) and growing season index (GSI) phenological models. MODIS start and end of season dates generally agreed with those obtained by the SW and GSI climate‐driven phenological models. However, phenological models provided erroneous results when applied in years with anomalous meteorological conditions. The relationships between interannual variability of the larch phenological cycle and climate were investigated by comparing the mean start and end of season yearly anomalies with air temperature anomalies. A strong linear relationship ( R 2 =0.91) was found between mean spring temperatures and mean start of season dates, with an increase of 1 °C in mean spring temperature leading to a 7‐day anticipation of mean larch bud‐burst date. Leaf coloring dates were found to be best related with mean September temperature ( R 2 =0.77), but with higher spring temperatures appearing to lead to earlier leaf coloring.

Effect of Early Introduction of Microencapsulated Diet to Larval Atlantic Halibut, Hippoglossus hippoglossus L. Assessed by Microarray Analysis - H. M. Murray; S. P. Lall; R. Rajaselvam; L. A. Boutilier; R. M. Flight; B. Blanchard; S. Colombo; V. Mohindra; M. Yúfera; S. E. Douglas (Marine Biotechnology, 2010)

Biochemical composition of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Paraná‐Río de la Plata Basin - E. D. Speranza; J. C. Colombo (Journal of Fish Biology, 2009)
The biochemical composition of muscle, liver and stomach contents of a detritivorous fish Prochilodus lineatus was analysed and compared to settling particles and sediments along pollution gradients over 1500 km of the Río de la Plata Basin to evaluate the effects of anthropogenic discharges in a detritus food chain. The stomach contents of P. lineatus collected in the polluted Metropolitan Buenos Aires coast were enriched in proteins, carbohydrates and lipids, similar to settling particulates collected in the sewer area, and two to five times higher than underlying sediments, supporting the interpretation that P. lineatus feeds on unconsolidated organic flocs freshly decanted from mixed industrial and sewage outfalls. Fish from Buenos Aires had consistently higher standard length ( L S ) and mass ( M T ) slopes ( b = 3·5), condition indexes ( K = 3·01 ± 0·47, mean ± s.d .) and muscle fat content (fat = 23·8 ± 13·8% wet mass, mean ± s.d .) relative to northern fish ( b = 2·7, K = 2·22 ± 0·39, fat = 3·4 ± 3·2% wet mass, respectively), suggesting that sewage‐derived organic matter was an enriched diet, which allowed an enhanced body mass gain and fat accumulation compared to organic‐poor vegetal detritus in the north Paraná area. Buenos Aires fish also showed higher hepato‐somatic indices (mean ± s.d . I H 1·41 ± 0·49 v. 0·70 ± 0·32, respectively), which correlated with their two to three orders of magnitude higher hydrocarbon and polychlorinated biphenyl (PCB) loads, suggesting an enhanced detoxifying metabolism. The northward migration of fatty P. lineatus was evidenced by the presence of clear outliers in the L S and M T relationship, K and fat content along the Paraná River.

European larch phenology in the Alps: can we grasp the role of ecological factors by combining field observations and inverse modelling? - M. Migliavacca; E. Cremonese; R. Colombo; L. Busetto; M. Galvagno; L. Ganis; M. Meroni; E. Pari; M. Rossini; C. Siniscalco; U. Morra di Cella (International Journal of Biometeorology, 2008)

Association Between the cfxA Gene and Transposon Tn4555 in Bacteroides distasonis Strains and Other Bacteroides Species - Livia Q. Ferreira; Katia E. S. Avelar; Jessica M. B. D. Vieira; Geraldo R. de Paula; Ana P. V. Colombo; Regina M. C. P. Domingues; Maria C. S. Ferreira (Current Microbiology, 2007)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Transpositional behaviour of an Ac/Ds system for reverse genetics in rice - R. Greco; P. B. F. Ouwerkerk; R. J. de Kam; C. Sallaud; C. Favalli; L. Colombo; E. Guiderdoni; A. H. Meijer; J. H. C. Hoge†; A. Pereira (Theoretical and Applied Genetics, 2003)

Sequence comparison and phylogenetic analysis of fish nodaviruses based on the coat protein gene - L. Dalla Valle; E. Negrisolo; P. Patarnello; L. Zanella; C. Maltese; G. Bovo; L. Colombo (Archives of Virology, 2001)

Effect of drying methods on retention of moist sucralfate gel properties - L. Maggi; P. L. Catellani; E. Fisicaro; P. Santi; F. Zani; G. Massimo; P. Colombo (AAPS PharmSciTech, 2000)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Characterization of a biofilter treating toluene contaminated air - V. Andreoni; G. Origgi; M. Colombo; E. Calcaterra; A. Colombi (Biodegradation, 1997)

G6PD Pinar del Ro: A new variant discovered in a Cuban family - R. Gonzlez; M. Wade; M. Estrada; E. Svarch; B. Colombo (Biochemical Genetics, 1977)